Identifying the communication of burnout syndrome on the Twitter platform from the individual, organizational, and environmental perspective - Ježková Petrů, Gabriela; Zychová, Kristýna; Drahotová, Kateřina; Kuralová, Kateřina; Kvasničková Stanislavská, Lucie; Pilař, Ladislav (Frontiers in Psychology, 2023)
Addressing the escalating prevalence of burnout syndrome, which affects individuals across various professions and domains, is becoming increasingly imperative due to its profound impact on personal and professional aspects of employees' lives. This paper explores the intersection of burnout syndrome and human resource management, recognising employees as the primary assets of organisations. It emphasises the growing importance of nurturing employee well-being, care, and work-life balance from a human resource management standpoint. Employing social media analysis, this study delves into Twitter-based discourse on burnout syndrome, categorising communication into three distinct dimensions: individual, organisational, and environmental. This innovative approach provides fresh insights into interpreting burnout syndrome discourse through big data analysis within social network analysis. The methodology deployed in this study was predicated upon the enhanced Social Media Analysis based on Hashtag Research framework and frequency, topic and visual analysis were conducted. The investigation encompasses Twitter communication from January 1st, 2019, to July 31st, 2022, comprising a dataset of 190,770 tweets. Notably, the study identifies the most frequently used hashtags related to burnout syndrome, with #stress and #mentalhealth leading the discussion, followed closely by #selfcare, #wellbeing, and #healthcare. Moreover, a comprehensive analysis unveils seven predominant topics within the discourse on burnout syndrome: organisation, healthcare, communication, stress and therapy, time, symptoms, and leadership. This research underscores the evolving landscape of burnout syndrome communication and its multifaceted implications for individuals, organisations, and the broader environment, shedding light on the pressing need for proactive interventions. In organisations at all levels of management, the concept of burnout should be included in the value philosophy of organisations and should focus on organisational aspects, working hours and work-life balance for a healthier working environment and well-being of employees at all levels of management.